2016
DOI: 10.1111/bpa.12361
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Hydrogen Sulfide Against Early Brain Injury and Secondary Cognitive Deficits Following Subarachnoid Hemorrhage

Abstract: Although the neuroprotective effects of hydrogen sulfide (H S) have been demonstrated in several studies, whether H S protects against early brain injury (EBI) and secondary cognitive dysfunction in subarachnoid hemorrhage (SAH) model remains unknown. This study was undertaken to evaluate the influence of H S on both acute brain injury and neurobehavioral changes as well as the underlying mechanisms after SAH. The H S donor, NaHS, was administered via an intraperitoneal injection at a dose of 5.6 mg/kg at 2 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 45 publications
(57 reference statements)
3
28
0
Order By: Relevance
“…BDNF polymorphisms predict a poor outcome in aneurysmal SAH patients 25. Moreover, BDNF was activated after cysteamine or N-acetyl serotonin derivative treatment in models of SAH 25,26. These data implicate the validity of our in vitro model, as well as the potential therapeutic effect of BDNF in SAH.…”
Section: Discussionsupporting
confidence: 53%
“…BDNF polymorphisms predict a poor outcome in aneurysmal SAH patients 25. Moreover, BDNF was activated after cysteamine or N-acetyl serotonin derivative treatment in models of SAH 25,26. These data implicate the validity of our in vitro model, as well as the potential therapeutic effect of BDNF in SAH.…”
Section: Discussionsupporting
confidence: 53%
“…ERK phosphorylation also results in the phosphorylation of the pro-apoptotic Bim protein (McCubrey et al, 2007), and then prevents Bax activation. The previous studies reported that the phosphorylation of ERK was decreased in brain after SAH insult and increase of its expression was associated with ameliorating neuronal cell death (Lin et al, 2009; Li et al, 2016). In agreement with these studies, we found that SAH insult decreased p-ERK level, while treatment with PUR significantly enhanced ERK phosphorylation.…”
Section: Discussionmentioning
confidence: 96%
“…Experimental animals were subjected to SAH by double blood injection method according to previous study (Li et al, 2016). Firstly, deep anesthesia was induced under 3.5% isoflurane and maintained the anesthesia state at a concentration of 2.5%.…”
Section: Methodsmentioning
confidence: 99%
“…NaHS treatment significantly improved brain edema and neurobehavioral function, and attenuated neuronal cell death in the prefrontal cortex, associated with a decrease in Bax/Bcl-2 ratio and suppression of caspase-3 activation after SAH [171]. …”
Section: Cell Death and H2smentioning
confidence: 99%